Psychophysical approaches to cognition - Algom, Daniel (Advances in psychology (Amsterdam, Netherlands), 1992)
Our lives are informed by perceptual and cognitive processes at all levels, from instrumental learning to metaphorical discourse to memorial representation. Yet, historically, these two branches of experimental psychology, perception and cognition, have developed separately using independent methods of experimentation and analysis. This volume is motivated by the assumption that a fundamental integration of the two fields is fruitful methodologically and indispensable theoretically. It explores how the notion of psychophysics aligned with cognitive processes shapes the study of perception and cognition, and illuminates a variety of contemporary research issues from a novel theoretical perspective. The papers raise conceptual and metatheoretical issues against the background of relevant empirical data. The authors provide a virtually narrative account of the most recent developments in their respective fields of expertise in psychophysics and cognitive psychology. Hence, this volume gives the interested reader an opportunity to reflect critically upon some of the current issues defining the two domains and their conjunction. Topics discussed include the psychology and psychophysics of similarity, the psychophysics of visual memory and cognitive factors in judgment. The emerging notion of cognitive psychophysics may well warrant the attention of experts in the field.